1998
DOI: 10.1117/12.316509
|View full text |Cite
|
Sign up to set email alerts
|

<title>ISOPHOT far-infrared serendipity sky survey</title>

Abstract: The ISOPHOT Serendipity Survey utilizes the slew time between ISO's pointed observations with strip scanning measurements of the sky in the far-infrared at 170 m. The slews contain information about two fundamentally different types of objects, namely (almost) unresolved galactic and extragalactic far-infrared sources as well as extended regions of galactic cirrus emission. Since the structure of the obtained data is almost unique, the development of dedicated software to extract astrophysically interesting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…First results from the 175µm serendipity survey indicate that this is a general result for normal spirals (Stickel et al 1999). However, Domingue et al (1999) argue from a direct comparison of visual and far-IR data in 3 overlapping galaxies against any dominant part of the dust mass being very much colder than 20 K. Particularly impressive is the case of M31 where Haas et al (1998b) have presented a 175µm map of the entire galaxy (Fig.2).…”
Section: Far-ir Emission: Cold Dust and Galactic Extinctionmentioning
confidence: 97%
See 1 more Smart Citation
“…First results from the 175µm serendipity survey indicate that this is a general result for normal spirals (Stickel et al 1999). However, Domingue et al (1999) argue from a direct comparison of visual and far-IR data in 3 overlapping galaxies against any dominant part of the dust mass being very much colder than 20 K. Particularly impressive is the case of M31 where Haas et al (1998b) have presented a 175µm map of the entire galaxy (Fig.2).…”
Section: Far-ir Emission: Cold Dust and Galactic Extinctionmentioning
confidence: 97%
“…With ISOCAM Gilmore & Unavane (1998) and Beichman et al (1999) have searched for IR halos in five edge-on galaxies. No off-disk halos are detected in any of them.…”
Section: Dark Matter In the Halos And Outer Parts Of Disksmentioning
confidence: 99%
“…deg at 90 µm by Efstathiou et al (2000) as part of the ELAIS survey. The ISOPHOT Serendipity Survey at 170 µm (Stickel et al 1998(Stickel et al , 2000 took advantage of ISO slews between targets to detect about 1000 sources between 1 and 1000 Jy.…”
Section: Introductionmentioning
confidence: 99%
“…There are two explanations for this: (1) the presence of synchrotron galaxies in equal numbers to dusty galaxies between 217 and 353 GHz which are not seen in the IRAS 60 μm selected sample; and (2) the cold dust component in the local Universe. Although the presence of cold dust has been known for some time (Stickel et al 1998;Dunne et al 2000), its effects may have been underestimated, as suggested in Planck Collaboration (2011g). There is a significant and largely unexplored cold (T < 20 K) component in many nearby galaxies.…”
Section: Planck Observations Of the Euclidean Levelmentioning
confidence: 97%